1999
DOI: 10.1152/ajpheart.1999.276.2.h359
|View full text |Cite
|
Sign up to set email alerts
|

Vasoconstrictor effect of endothelin-1 in human skin: role of ETAand ETBreceptors

Abstract: The aim of this project was to investigate the role of ETA and ETB receptors in the mediation of endothelin (ET)-1-induced vasoconstriction in human skin. This information should provide important insights into the design of pharmacological intervention against skin vasospasm induced by ET-1 in peripheral vascular disease or surgical trauma. Vasoconstriction in response to intra-arterial drug infusion in isolated perfused human skin flaps (8 × 18 cm) derived from dermolipectomy specimens was assessed by studyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 40 publications
4
35
0
Order By: Relevance
“…The dose-response effect of L-type Ca 2ϩ channel blockers on skin hemodynamics and viability in flap surgery has yet to be investigated. It has been demonstrated that the vasoconstrictor effect of ET-1 is mediated by ET A receptors, with little participation from ET B receptors (30). Therefore, selective ET A -receptor antagonists may also be used as a combined treatment for skin flap vasospasm.…”
Section: Discussionmentioning
confidence: 99%
“…The dose-response effect of L-type Ca 2ϩ channel blockers on skin hemodynamics and viability in flap surgery has yet to be investigated. It has been demonstrated that the vasoconstrictor effect of ET-1 is mediated by ET A receptors, with little participation from ET B receptors (30). Therefore, selective ET A -receptor antagonists may also be used as a combined treatment for skin flap vasospasm.…”
Section: Discussionmentioning
confidence: 99%
“…Mo re re cen tly, ET R Bs ha ve al so been iden ti fi ed in vas cu lar smoo th mus cle cel ls, and these two re cep to rs me dia te va so con stric tion (43). The pre sen ce of ETRB wi th the va ria tion of ETRA/ ETRB ra tio was de tec ted on en dot he lial cel ls and it is hig her in ar te ries than in vei ns.…”
Section: Eff E Cts Of En Dot He Lin On Smoo Th Mus Cle Cel Ls and Carmentioning
confidence: 99%
“…This tissue is normally discarded in abdominal dermolipectomy (Kreidstein et al, 1991). Several techniques have confirmed the perfusion of the flap (Black et al, 2001;Kreidstein et al, 1995;Lipa et al, 1999;Miland et al, 2008). Miland and colleagues (2008) confirmed the suitability of the dynamic infrared thermography (DIRT) to monitor skin flap perfusion and to differentiate between well and less perfused areas.…”
Section: Introductionmentioning
confidence: 98%